MILIARY TUBERCULOSIS COMPLICATED BY STAPHYLOCOCCAL SEPSIS - Stanojevic, Dragan; Antonijevic, Gordana; Vojinovic, Radisa; Opancina, Valentina (Medicinski časopis, 2018)
Milliary tuberculosis is potentially fatal due to the massive dissemination of Mycobacterium tuberculosis. Since immunoregulatory mechanisms are disrupted, during the evolution of milliary tuberculosis, nonspecific infections develop and sometimes even sepsis. Sepsis is a rare complication in immunocompetent patient. In patients with disseminated tuberculosis, close attention and care should be made if clinical presentation suggests sepsis. In this paper, we present a patient with whom we simultaneously diagnosed miliary tuberculosis and staphylococcal sepsis on admission in 2007. Miliary tuberculosis was first proven by histopathologically by transbronchial lung biopsy, and later confirmed by microbiological and ophthalmologic examination. Two blood samples from different punction locations had isolated Staphylococcus epidermidis.  Right after the admission, medical team started treatment of septic shock and respiratory failure with the oxygen therapy, parenteral rehydration, vasoactive agents with a combination of selected antibiotics and antituberculotic drugs. After recovery, treatment was continued in extensive phase using combination of antituberculotics and patient was discharged to be home treated and checked by antituberculous ambulant.